Satisfying visitors' needs: What to resort to - Adam H. Viljoen; Martinette Kruger; Melville Saayman (South African Journal of Business Management, 2019)
Background: Over centuries resorts across the world have played a pivotal role in tourism and can even be seen as the backbone of tourism as we know and comprehend it today. South Africa is no different, and the country has numerous resorts attracting thousands of visitors annually. Hence, there is strong competition among the different resorts.Objectives: Based on the above, this research aimed to obtain an understanding of the resort travel market in South Africa by investigating if different resorts attract different types of visitors.Method: This is an under-researched topic, yet the wide variety of resorts provides ample opportunities for investigation. This article identifies four important travel motives of resort visitors and provides insight into the importance of resort amenities by outlining five essential resort attributes.Results: This article finds that different resorts attract different markets, which influences the marketing and management opportunities of each resort.Conclusion: From the results, viable marketing and management recommendations are provided.
Keywords: 650